Anthropology and the individual : a material culture perspective - Miller, Daniel, 1954- (Materializing culture., 2009)
Anthropology is usually associated with the study of society, but the anthropologist must also understand people as individuals. This study demonstrates how methods of social analysis can be applied to the individual, while remaining entirely distinct from psychology and other perspectives on the person.